Distribution area of the two floral morphs of Nigella damascena L. (Ranunculaceae): a diachronic study using herbarium specimens collected in France. Issue 3 (2nd October 2018) - Damerval, Catherine; Ben Othman, Wafa; Manicacci, Domenica; Jabbour, Florian
Abstract: Perianth dimorphism in Nigella damascena (Ranunculaceae) has been documented for four centuries, and its genetic basis started to be studied almost a century ago. Based on herbarium collections, we reconstructed the evolution of the distribution area of the wild-type (perianth composed of a calyx and nectariferous petals) and mutant (apetalous) floral morphs in mainland France over the last two centuries. We showed that the collection localities of the wild-type morph are mostly concentrated in the southern coastal areas of France, whereas the collection localities of the mutant morph were less numerous but more scattered in France. The collection effort of both morphs peaked in the second half of the nineteenth century and continuously decreased afterwards. Results are interpreted taking into account the biases in the constitution of a herbarium collection. Knowledge about the spatial distribution and the frequency of occurrence of wild-type and mutant populations through time will help botanists and evolutionary biologists investigate the origin and ecological grounds for the maintenance and propagation of the apetalous morph in the wild.